The Effect of Different Temperatures on Addition of Powdered Lactobacillus plantarum Dad-13 on Peanut Chocolate Jam Towards Total Lactic Acid Bacteria (LAB), Sublethal Injury, pH, and Total Acids - Rizka Amalia Rahayu; Rafli Zulfa Kamil; Anang Mohamad Legowo (Diponegoro University, 2024)
Lactobacillus plantarum Dad-13 is an indigenous probiotic that was isolated from Dadih. Peanut chocolate jam has the potential to be developed into a probiotic food product. However, peanut chocolate jam involves a heating process which can affect the number of probiotics and their metabolic processes. This research aims to determine the optimal temperature of L. plantarum Dad-13 probiotic powder in addition to peanut chocolate jam products. The different temperatures of probiotic powder L. plantarum Dad-13 addition at 30 oC, 40 oC, 50 oC, and 60 oC were used to measure total lactic acid bacteria (LAB), sublethal injury, pH value, and total acids. Total lactic acid bacteria and sublethal injury were measured by Total Plate Count (TPC), pH value was measured by pH meter and total acids were analyzed using the titration method. Results show significant differences (p<0,05) on total lactic acid bacteria (LAB) and sublethal injury. Total lactic acid bacteria (LAB) resulting in a value of 8.04±0.02 to 7.67±0.05 and sublethal injury 0.04±0.01 to 0.26±0.03. Meanwhile, no significant differences (p>0,05) in pH value (7.20±0.16 to 7.30±0.15) and total acids (0.09±0.01 to 0.08±0.01). The best temperature of L. plantarum Dad-13 probiotic powder addition on peanut chocolate jam was at 30–40 oC because it showed the highest amount of total lactic acid bacteria (LAB) and the least sublethal injury.